Defining Risk of Postoperative Obstructive Sleep Apnea in Patients With 22q11.2DS Undergoing Pharyngeal Flap Surgery for Velopharyngeal Dysfunction Using Polysomnographic Evaluation. (July 2020) - Lee, Alfred; Chang, Brian L.; Solot, Cynthia; Crowley, Terrence B.; Vemulapalli, Vamsee; McDonald-McGinn, Donna M.; Maguire, Meg Ann; Mason, Thornton B. A.; Elden, Lisa; Cielo, Christopher M.; Jackson, Oksana A.
Objective: To determine pre- and postoperative prevalence of obstructive sleep apnea (OSA) in patients with 22q11.2 deletion syndrome (DS) undergoing wide posterior pharyngeal flap (PPF) surgery for velopharyngeal dysfunction (VPD). Design: Retrospective study using pre- and postoperative polysomnography (PSG) to determine prevalence of OSA. Medical records were reviewed for patients' medical comorbidities. Parents were surveyed about snoring. Setting: Academic tertiary care pediatric hospital. Patients: Forty patients with laboratory confirmed 22q11.2DS followed over a 6-year period. Interventions: Pre- and postoperative PSG, speech evaluation, and parent surveys. Main Outcome Measure: Severity and prevalence of OSA, defined by obstructive apnea hypopnea index (OAHI), before and after PPF surgery to determine whether PPF is associated with increased risk of OSA. Results: Mean OAHI did not change significantly after PPF surgery (1.1/h vs 2.1/h, P = .330). Prevalence of clinically significant OSA (OAHI ≥ 5) was identical pre- and postoperatively (2 of 40), with both cases having severe-range OSA requiring positive airway pressure therapy. All other patients had mild-range OSA. Nasal resonance was graded as severe preoperatively in 85% of patients. None were graded as severe postoperatively. No single patient factor or parent-reported concern predicted risk of OSA (OAHI ≥ 1.5). Conclusions: Patients with 22q11.2DS are medically complex and are at increased risk of OSA at baseline. Wide PPF surgery for severe VPD does not significantly increase risk of OSA. Careful perioperative planning is essential to optimize both speech and sleep outcomes.